(untitled) (Global Journal of Management and Business Research, 2022)
Over the past few years the world economy has been declining and the recession has caused inflation unemployment and a decline in financial well-being The decline in financial well-being has harmful effects on mental and physical health It creates problems of stress anxiety depression and suicide in our society Taft et al 2013 Financial literacy has become a much-discussed topic in recent years for the financial empowerment of people and their lives